Investigating the Impact of Social Media Algorithms and Echo Chambers on Political Belief and behaviors - Ihsanullah; Shabeer; Faisal Shahzad (Journal of Peace, Development and Communication, 2023)
In this modern period, most of the politicians and political parties have started using social networking media for campaigning, promoting ideologies and gaining support from the masses. On the other hand, most social networking media users are also taking advantage of this political avenue. Therefor the key intention of the study is investigate the Impact of Social Media Algorithms and Echo Chambers on Political Belief and behaviors. So a survey method is applied to gather the response from the Peshawar Division the copies of questionnaire were distributed among 200 students of universities who is the users of social networking media. The questionnaire was pre-tested on a small group of respondents to ensure its reliability and validity. The findings suggest that social networking media has a strong influence on the social and political learning of its users. The study concludes that social media algorithms have a strong influence on political socialization and voter behavior.